The grand Mosque in Yogyakarta Indonesia - Edrees, Munichy Bachron 1952- (1986)
The Quba Mosque which was constructed by the Prophet Mohammed in 622 A.D. constitutes the best example of the Mosque for the members of the Moslem community and for the next generations. Its design features cover the following: its construction was based on nTakwan 9devotion) to Allah; simply, it means it was constructed by using local technology and local building materials; there is clarity of function and objective in the plan; it houses activities for Ibadah (religious) and Mu'amalah (social) functions. Existing mosques, from a world survey, show that the architecture features are the following: generally, the form of the mosque does not follow its function; mosque have domes and high minarets, which reflect the vertical elements; they have domes in the middle of the space, so that it makes the orientation of jama'ah (congregation upward not in the Mikhrab; there are so many columns in the middle of the space which disturb the row of jama'ah. Therefore, in planning and designing a mosque, it should incorporate the Main Basis of the Philosophy. These are: the construction of mosque should be based on nTakwan, the construction of mosques should be because of Allah and only for Allah; it should be free form nsyirikn., the mosque should be free from elements which stimulate the presence of nsyirikn, like: statues, pictures, and so on; Ibadah and Mu'amalah should be equally integrated, it means Mu'amalah activities as supporting factors of Ibadah activities, and Mu'amalah activities as jama'ah puller; it should apply the simplicity principle, use of cheap building materials and those easily found in the market, but considering aesthetic features nevertheless;, by applying principle of economical and optimum aesthetics; it should consider and apply the intimate, openness and equality principle, the mosque should be able to give opportunities for intimate situations. It should necessary to avoid the presence of columns in the middle of the space which do not give the impression of communication, should reflect an open situation, which is easily achieved by using partition walls which are optically transparent or give impression of transparency, the presence of values leading to unity of space will give the expression of unity for jam'ah in it; the mosque should be oriented to Mecca; should pat attention to the benefit of the iron and steel which are of great benefit and advantage to men; should pay attention to the benefit of the outdoor space as a part of the universe which was created by Allah; should hold the integration of the physical form to the function of a mosque, should have a feeling of greatness and monumentality giving a grand scale as compared to the human scale; should be near Moslem communities; should be neutral from all other religious services and religions.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman.
Keywords: Mosques -- Yogyakarta -- Designs and plans. -- Indonesia; Architecture, Islamic -- Indonesia